2016
DOI: 10.1017/s1047951116001967
|View full text |Cite
|
Sign up to set email alerts
|

Extensive coronary and systemic arterial aneurysm development in severe refractory Kawasaki disease

Abstract: We describe the case of an 8-week-old infant with late presentation of severe refractory atypical Kawasaki disease. In addition to developing giant coronary arterial aneurysms and coronary thrombosis, she formed extensive bilateral arterial aneurysms throughout her systemic circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…Although only 23 patients with SAAs were included in this study (because of the rarity of the disease), it is still the largest sample size we are aware of, and may, in part, reflect the current incidence and early outcome of SAAs. Early screening of SAAs by full-body MRA in patients with medium or giant CAAs can detect clinically significant SAAs more promptly than PA, 6,8,24 which is essential for the management of patients with KD. Careful physical examination for pulsatile masses by palpation of the axillary, brachial, abdominal, and inguinal regions is also important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although only 23 patients with SAAs were included in this study (because of the rarity of the disease), it is still the largest sample size we are aware of, and may, in part, reflect the current incidence and early outcome of SAAs. Early screening of SAAs by full-body MRA in patients with medium or giant CAAs can detect clinically significant SAAs more promptly than PA, 6,8,24 which is essential for the management of patients with KD. Careful physical examination for pulsatile masses by palpation of the axillary, brachial, abdominal, and inguinal regions is also important.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Since the advent of intravenous immunoglobulin (IVIg) therapy, almost all English-language literature on KD-related SAAs consist of case reports revealing that axillary, subclavian, brachial, iliac, and femoral arteries are common sites of involvement. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] To date, there are only 2 reports from the same Japanese medical center in which authors reported the incidence of SAAs in patients with KD, but, in fact, less than half of their patients with KD were screened for SAAs; it was during their study that they found that only patients with giant CAAs developed SAAs. 3,4 Although it is a reasonable assumption that there is a concomitant decrease in SAA formation with early IVIg therapy, as well as a decrease in CAAs, there are no published data to support this.…”
mentioning
confidence: 99%
“…After excluding unrelated studies and duplicates, 60 articles were included. After cross-referencing from the included studies, a total of 61 articles describing CAA with multiple coexisting aneurysms were finally included, [ 3 63 ] with a total of 76 patients (age: 37.4 ± 26.5 years; male: 58 [76.3%]). The patients’ ages ranged from 7 weeks to 81 years, and 24 patients were less than or equal to 18 years of age.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to CAAs commonly seen in KD, non-coronary systemic artery aneurysms can also be a sequela of KD. In previous reports on SAAs in KD [ 3 – 5 , 7 , 8 , 10 ], most of SAAs occured in infants, and in patients with untreated KD, IVIG-resistant KD or severe refractory KD, which are all at a higher risk of developing CAAs. In this case, although there was somewhat of a delay in the diagnosis and treatment of the patient, on the 10th day of onset, he responded to one dose of IVIG.…”
Section: Discussionmentioning
confidence: 99%